Determination of concentration levels of toxic elements and radon in drinking waters consumed in Kastamonu province, Turkey - Alzaridi, F.M.N.S.; Kurnaz, A. (Informa UK Limited, 2020)
In this study, the concentrations of potentially toxic elements (Cd, Co, Cr, Cu, Fe, Ni, Mn, Zn, Pb, and As) and radon (222Rn) in forty-five drinking water (tap and bottled water) samples consumed ...
Keywords: 6. Clean water